Effects of different concentrations of Aspergillus niger on fermentation characteristics and nutritive value of Napier grass silage: Quality of Napier grass silage treated with Aspergillus niger (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Napier grass is considered to be low-quality grass due to its low nutritional value. This study was aimed at investigating the effect of Aspergillus niger on the improvement of Napier grass silage quality. The plants were mixed with 7% molasses and A. niger at a rate of 0 (T0), 106 (T1) and 107 spores/ml (T2). Each kg of plant materials was mixed with 10.7ml fungal substrate and ensiled for 45 days. According to the results of this study, the pH tended to decrease with an increased rate of A. niger, while the lactic acid content tended to increase. The T1 silage showed lower (p0.05) differences were observed on other proximate components. An increasing trend was observed in crude protein content with an increasing rate of A. niger, while no consistent trend was observed in crude fibre content. In conclusion, A. niger could be used as an additive to enhance the silage quality, but further research is needed to know the nature of the mode of action of A. niger in silage.
Keywords: Colony forming unit; Crude protein; Lactic acid; pH; Proximate analysis